A study protocol for a randomized controlled trial on effect of yoga nidra on the levels of stress, anxiety and depression in patient released from Hansen’s disease Treatment - Rathinam, Karthikeyan; Subramanyam, Indira Devi; Annamalai, Gayathri; Poornachandran, Kumaresan; Murugesan, Priyanka (Indian Journal of Integrative Medicine, 2025)
Background: Hansen’s disease is a chronic illness that dates back thousands of years and is now regarded as a neglected tropical disease. In ancient medicinal texts, the term “Kushtha” has been mentioned. Hansen’s disease and mental health issues have a close relationship that might result in chronic comorbidity. Hansen’s disease affects 0.4 people out of every 10,000 in the nation. Along with multidrug therapy, they also require mind-body interventions. Yoga Nidra is a guided relaxation technique in yogic practices. No scientific evidence is available for yoga nidra in Hansen’s disease (RFT). This study aims to find the effect of yoga nidra on stress, depression, and anxiety levels in Hansen’s disease (RFT). Objective: The objective of the study is to assess the levels of stress, depression and anxiety using DASS21 scale and PHQ9 scales. In addition, the quality of life will be assessed using the WHOQOL-BREF questionnaire and the sleep quality using PSQI scale. Materials and Methods: This is a randomized controlled trial with sample size of 80. The subjects will be divided into two groups, namely, the intervention group and the control group with 40 subjects each. Participants will be classified as PAL (People affected by Leprosy) or RFT (released from treatment) between the age group 35 to 60 years of both genders will be included. In the intervention group, subjects will be practicing Yoga nidra for 30 minutes, 5 days a week for 12 weeks. Whereas, conventional treatment will be followed in the control group. The levels of stress, anxiety, depression and sleep quality will be assessing before and after the intervention with the DASS 21, PHQ-9, WHOQOL and PSQI scale. Results: Data will be analysed using statistical package for social sciences version 16. In this study, a p-value of